Perjanjian Buy Back Guarantee Terhadap Kredit Pemilikan Rumah Bersubsidi - Mulyadi, Fani; Mahmudah, Siti (Notarius, 2025)
ABSTRACTPayments using credit lines are often made now for household needs, including public housing loans. Developers collaborate with financing institutions, for example banks, to provide public housing credit. The creditor and developer enter into a buy back guarantee agreement to overcome the risk of default or bad credit. This article aims to determine the legal protection provided by buy back guarantee agreements for subsidized home ownership loans that are in default or bad credit. This research was conducted using a normative juridical approach, with the results of the research being that legal protection was given to all parties, only the banking party received the greatest protection in the agreement.Keywords: Account Receivable; Buy Back Guarantee.ABSTRAKPembayaran dengan jalur kredit tidak jarang dilakukan sekarang untuk kebutuhan rumahtangga, termasuk juga dengan kredit perumahan rakyat. Developer bekerjasama dengan Lembaga Pembiayaan contohnya Bank untuk memberikan kredit perumahan rakyat. Pihak kreditur dan pihak developer melakukan perjanjian buy back guarantee untuk mengatasi resiko terjadinya wanpretasi atau kredit yang macet. Artikel ini bertujuan untuk mengetahui perlindungan hukum yang diberikan oleh perjanjian buy back guarantee dalam kredit pemilikan rumah bersubsidi yang mengalami wanprestasi atau kredit macet. Penelitian ini dilakukan dengan pendekatan yuridis normatif. Hasil penelitian ini yaitu perlindungan hukum diberikan kepada semua pihak hanya saja pihak perbankan yang menerima perlindungan terbesar dalam perjanjian tersebut.Kata Kunci: Kredit Macet; Buy Back Guarantee.